Integrasi Otomasi IoT Berbasis Sensor untuk Pemberian Pakan dan Pembersihan pada Sistem Sangkar Burung Pintar - Muhammad Farid Rahman; Muhammad Khoirul Anam; Faiz Husnayain; Rifki Suwandi (Jurnal Otomasi Kontrol dan Instrumentasi, 2026)
Pet songbirds require consistent care, but prolonged owner absence often leads to irregular feeding and poor sanitation. Existing IoT-based bird care systems remain fragmented, focusing primarily on single aspects like feeding, while sanitation mechanisms are often mechanically complex or ignored. This study proposes an integrated IoT autonomous bird cage that uniquely combines feeding, watering, and a simplified stepper-motor-driven brush-and-spray cleaning mechanism into a single framework. Controlled by an Arduino Uno R4 WiFi and an RTC module for precise offline scheduling, the system utilizes a robust capacitive sensor for water monitoring to overcome the unreliability of standard acoustic sensors in confined micro-climates. Experimental testing demonstrated sub-centimeter sensor accuracy and a 0% failure rate for automated water refilling, outperforming the 20% failure rate observed in the ultrasonic feed sensor. Furthermore, the novel cleaning subsystem achieved a 94% quantitative waste removal efficiency. These results confirm the proposed architecture is a reliable, comprehensive solution that significantly reduces manual intervention in smart pet management.